2010
DOI: 10.22358/jafs/66319/2010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grain polyphenols and the addition of vitamin E to diets enriched with α-linolenic acid on the antioxidant status of pigs

Abstract: The aim of this study was to determine the antioxidant status and blood lipid profile of pigs fed diets enriched with α-linolenic acid (ALA) and containing two sets of antioxidants: phenolic compounds of diet components (barley, triticale, naked oat and buckwheat by-products) only, or phenolic compounds and vitamin E supplementation. A three-factorial experiment was performed on growing-finishing barrows (6-7 pigs per group) fed individually diets supplemented with 3% linseed oil, formulated as isoenergetic, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In a study by Maghin et al (2016), dietary supplementation with algae-derived polyphenols did not affect the antioxidant status of pigs, but increased the number of piglets born alive in the group of sows receiving the above feed additive relative to the control group. Flis et al (2010) found that diets rich in a-linolenic acid (ALA) with a higher content of polyphenols derived from barley and triticale increased the activity of SOD and GSH-Px and serum TAS values in pigs. In another experiment, growing-finishing pigs whose diets were supplemented with vitamin E were characterised by higher SOD activity and tocopherol levels than in the remaining groups (Sobotka et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Maghin et al (2016), dietary supplementation with algae-derived polyphenols did not affect the antioxidant status of pigs, but increased the number of piglets born alive in the group of sows receiving the above feed additive relative to the control group. Flis et al (2010) found that diets rich in a-linolenic acid (ALA) with a higher content of polyphenols derived from barley and triticale increased the activity of SOD and GSH-Px and serum TAS values in pigs. In another experiment, growing-finishing pigs whose diets were supplemented with vitamin E were characterised by higher SOD activity and tocopherol levels than in the remaining groups (Sobotka et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was hypothesized that adding vitamin E to the flaxseed diet would lead to improved results for oxidative stress and the prevention of atherosclerotic lesions as there is evidence that the consumption of flaxseed reduces vitamin E ( 19 ), and only vitamin E supplementation is able to restore the plasma concentration ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…SDG has demonstrated extreme radical scavenging activity, thereby protecting polyunsaturated fatty acids from oxidation ( 16 18 ). Despite the beneficial effects of SDG, flaxseed consumption has been found to significantly reduce α- and γ-tocopherol concentrations in rats ( 19 ) and only vitamin E supplementation was able to restore the plasma concentrations ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects of vitamin E additives (of various chemical forms added at different concentrations) on pork quality and on anti-oxidative stability of muscles have been reported in many articles Jensen et al 1997;Lauridsen et al 2000;Lahučk y et al 2000;Bahelka et al 2004;Guo et al 2006;Janz et al 2008;Bahelka et al 2010;Bahelka et al 2011;Waszkiewicz-Robak et al 2015). Numerous pure pig breeds (Berkshire, Hampshire, White Meaty, Large White) and various hybrids (Large White 3 Landrace 3 Duroc, Hybrid Goland pig [Heavy pig], Landrace 3 Hampshire 3 Pietrain, Landrace 3 Large White, Duroc 3 large White 3 Landrace, Landrace 3 Yorkshine) were studied (Asghar et al 1991a,b;Monahan et al 1992;Anderson et al 1995;Lanari et al 1995;Morrissey et al 1996;Wang et al 1996;Corino et al 1999;Lauridsen et al 1999;Rey et al 2001;Pieszka et al 2006;Niculita et al 2007;Flis et al 2010;Bahelka et al 2011). In majority of cases impact of vitamin-rich feed on level of vitamin E in raw meat was assessed, while loss of the vitamin during meat processing was studied by a few authors only.…”
Section: Introductionmentioning
confidence: 99%